Importance of TLR2 on hepatic immune and non-immune cells to attenuate the strong inflammatory liver response during Trypanosoma cruzi acute infection. - Eugenio Antonio Carrera-Silva; Natalia Guiñazu; Andrea Pellegrini; Roxana Carolina Cano; Alfredo Arocena; Maria Pilar Aoki; Susana Gea (Public Library of Science (PLoS), 2010)
BACKGROUND: Toll-like receptors (TLR) and cytokines play a central role in the pathogen clearance as well as in pathological processes. Recently, we reported that TLR2, TLR4 and TLR9 are differentially modulated in injured livers from BALB/c and C57BL/6 (B6) mice during Trypanosoma cruzi infection. However, the molecular and cellular mechanisms involved in local immune response remain unclear. METHODOLOGY/PRINCIPAL FINDINGS: In this study, we demonstrate that hepatic leukocytes from infected B6 mice produced higher amounts of pro-inflammatory cytokines than BALB/c mice, whereas IL10 and TGFβ were only released by hepatic leukocytes from BALB/c. Strikingly, a higher expression of TLR2 and TLR4 was observed in hepatocytes of infected BALB/c mice. However, in infected B6 mice, the strong pro-inflammatory response was associated with a high and sustained expression of TLR9 and iNOS in leukocytes and hepatic tissue respectively. Additionally, co-expression of gp91- and p47-phox NADPH oxidase subunits were detected in liver tissue of infected B6 mice. Notably, the pre-treatment previous to infection with Pam3CSK4, TLR2-agonist, induced a significant reduction of transaminase activity levels and inflammatory foci number in livers of infected B6 mice. Moreover, lower pro-inflammatory cytokines and increased TGFβ levels were detected in purified hepatic leukocytes from TLR2-agonist pre-treated B6 mice. CONCLUSIONS/SIGNIFICANCE: Our results describe some of the main injurious signals involved in liver immune response during the T. cruzi acute infection. Additionally we show that the administration of Pam3CSk4, previous to infection, can attenuate the exacerbated inflammatory response of livers in B6 mice. These results could be useful to understand and design novel immune strategies in controlling liver pathologies.